Dependence of the ignition temperature of coals on their properties - Miroshnichenko, Denis; Kaftan, Yuriy; Desna, Natali; Nazarov, Valeriy; Senkevich, Irina; Nikolaichuk, Yuriy (Lviv Politechnic Publishing House, 2018)
Проаналізовані реакції вугілля з реагентами, які використовуються для визначення температури займання неокисненого вугілля. Визначені величини температур займання вугілля України, Росії, Канади, Австралії, Чехії, Польщі та Індонезії. Оцінено вплив складу, структури та властивостей вугілля на температуру його займання. Встановлено, що температура займання неокисненого вугілля щільно пов’язана з вмістом органічного та ароматичного карбону, структурним параметром, що характеризує ступінь насичення органічної маси вугілля, а також показниками середнього коефіцієнту відбиття вітриніту та виходу летких речовин.

The reactions of coal with the materials used in determining the ignition temperature of unoxidized coal were analyzed. The ignition temperatures of various types of coal from Ukraine, Russia, Canada, Australia, the Czech Republic, Poland, and Indonesia were determined. The influence of the composition, structure, and properties of the coal on its ignition temperature was assessed. The ignition temperature of the unoxidized coal was found to be closely related to the content of organic and aromatic carbon, the structural parameter characterizing the degree of saturation of the coal organic mass, and also the mean vitrinite reflectance coefficient and the volatile matter.
Залежність температури займання вугілля від його властивостей
Keywords: вугілля; температура займання; властивості вугілля; математичні рівняння; coal; ignition temperature; coal properties; mathematical equations